In vitro evaluation of a novel nanostructured Ti-36Nb-6Ta alloy for orthopedic applications - Voltrova, Barbora; Jarolimova, Petra; Hybasek, Vojtech; Blahnova, Veronika Hefka; Sepitka, Josef; Sovkova, Vera; Matějka, Roman; Daniel, Matej; Fojt, Jaroslav; Filova, Eva (Nanomedicine (London, England), 2020)
Aim: To evaluate the impact of a nanostructured surface created on β-titanium alloy, Ti-36Nb-6Ta, on the growth and differentiation of human mesenchymal stem cells. Materials & methods: The nanotubes, with average diameters 18, 36 and 46 nm, were prepared by anodic oxidation. Morphology, hydrophilicity and mechanical properties of the nanotube layers were characterized. The biocompatibility and osteogenic potential of the nanostructured surfaces were established using various in vitro assays, scanning electron microscopy and confocal microscopy. Results: The nanotubes lowered elastic modulus close to that of bone, positively influenced cell adhesion, improved ALP activity, synthesis of type I collagen and osteocalcin expression, but diminished early cell proliferation. Conclusion: Nanostructured Ti-36Nb-6Ta with nanotube diameters 36 nm was the most promising material for bone implantation.
Keywords: mechanical properties; Humans; osteogeneze; povrchové vlastnosti; Alloys; Osteogenesis; osteogenic differentiation; proliferation; anodization; osteoblasty; nanotubes; nanotrubičky; Microscopy, Electron, Scanning; Cell Adhesion; lidé; Osteoblasts; proliferace buněk; titan; biocompatibility; Titanium; Nanotubes; mikroskopie elektronová rastrovací; Cell Proliferation; beta titanium alloy; hMSC; slitiny; buněčná adheze; adhesion; Surface Properties